MODERN METHODS OF TEACHING ENGLISH - Atajanova Shakhodat Kahramanovna (Journals Park Publishing, 2024)
The article scientifically substantiates the features of teaching English in vocational schools. One of the pressing problems is the training of young people who are able to speak foreign languages to ensure the development of Uzbekistan at the international level, to be courageous, competent, knowledgeable and significant specialists who have their own independent opinion.
Keywords: vocational schools, secondary schools, English language, world community, foreign countries, economics, politics, custo.